Transgenics: Colored Fluorescent Silk Made by Transgenic Silkworms (Adv. Funct. Mater. 42/2013). (13th November 2013) - Iizuka, Tetsuya; Sezutsu, Hideki; Tatematsu, Ken‐ichiro; Kobayashi, Isao; Yonemura, Naoyuki; Uchino, Keiro; Nakajima, Kenichi; Kojima, Katsura; Takabayashi, Chiyuki; Machii, Hiroaki; Yamada, Katsushige; Kurihara, Hiroyuki; et al.
<x xml:space="preserve">Abstract</x> Transgenic silkworms are adapted for mass production of recombinant silks by T. Tamura and co‐workers. They have fluorescent colors and a large amount of the cocoons can be harvested. Cooking and reeling methods are established on page 5232 for the production of recombinant silks without any loss of the fluorescent color. The mechanical properties of the modified silk are similar to those of commercial silks, and thus the modified silks can be used for making fabrics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>